Global supply chains and multimodal logistics emerging research and opportunities - Sinha, Deepankar, 1962- (Advances in logistics, operations, and management science (ALOMS) book series., 2019)
"This book provides concepts of global logistics and describes how it varies with domestics logistics. It also examines the concept of INCO (International commercial terms) and its relevance with logistics decisions"--